واقع المصارف الإسلامية العاملة في سورية في ظل الأزمة الراهنة (خلال الفترة 2011-2014) - العمار, رضوان; صوفان, دينا (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يتناول هذا البحث دراسة موضوع يعد من أهم المواضيع المعاصرة, وهو واقع المصارف الإسلامية التي أثبتت حضوراً متميزاً منذ بداياتها الأولى من خلال التنامي المتزايد في الحصة السوقية وارتفاع أداء وحجم الأعمال المصرفية وتعدد أساليب التمويل الإسلامية.يركز هذا البحث على دراسة واقع المصارف الإسلامية بشكل عام من حيث عرض مفهومها، ونموذج المصرف الإسلامي في فكر المؤسسين ومدى التطبيق العملي لهذا الفكر, ثم البحث عن واقع المصارف الإسلامية في الجمهورية العربية السورية- على الرغم من حداثة عهدها ومرور المنطقة بأزمة حالية - من خلال عرض نشأتها, تطورها, أداء المصارف العاملة فيها، ومعرفة مدى التزامها بتطبيق فكر المؤسسين. ثم رصد آثار الأزمة التي تمر بها المنطقة منذ عام2011 في أداء هذه المصارف ( الموارد- التمويل- الأرباح ) من خلال تحليل بياناتها المالية ومعرفة مدى حقيقة الأرقام الايجابية الظاهرة في تلك البيانات خاصة الأرباح المرتفعة, ومن ثم تقديم بعض المقترحات لكيفية مواجهة تأثيرات الأزمة عليها والتوصيات التي يمكن الاستفادة منها لتطوير عمل المصارف الإسلامية السورية. وإن أهم ما توصل إليه البحث أن واقع المصارف الاسلامية عامة والسورية خاصة لا يحاكي فكر المؤسسين، كما أن نسب توظيف الموارد في المصارف الإسلامية السورية خلال فترة الأزمة الراهنة كانت منخفضة على الرغم من ارتفاع حجم كل من الموارد و التمويلات، والأرباح التي حققتها هذه المصارف خلال الأزمة هي أرباح غير حقيقية.This research handles one of the most important and contemporary subjects. It is the status of Islamic banks, which proved a significant presence since its earliest beginning, through increasing growth in market share, high performance and amount of banking businesses, and multiple methods of Islamic funding.This research focuses on studying the conditions of Islamic banks in general, in terms of offering its concept, principles of founders, and the practical application of these principles in bank business, then examining the conditions of Islamic banks in the Syrian Arab Republic in spite of its newness and the crisis the area is going through. This would be done through displaying its origin, development, the performance of banks operations in it, and knowing if these banks are committed to the principles of founders ,then monitoring the crisis’ effects in the area since 2011 on the performance of these banks (Financial resources - Funding- Profits) through analyzing its financial statements and knowing the truthfulness of these positive data mentioned in these statements specially the highest profits. The study also attempts to offer some suggestions to face the effects of the crisis and straighten the work of these banks.The most important search results is that the conditions of Islamic banks in general and Syrian Islamic banks in particular did not match the principles of founders , financial resources employment ratios were low despite the rise of resources and funds , and the profits made by Syrian Islamic banks during this crisis are not real profits.